2006
DOI: 10.1002/chem.200500986
|View full text |Cite
|
Sign up to set email alerts
|

A Photocontrolled β‐Hairpin Peptide

Abstract: Beta-hairpins constitute the smallest beta-type structures in peptides and proteins. The development of highly stable, yet monomeric beta-hairpins based on the tryptophan zipper motif was therefore a remarkable success [A. G. Cochran, N. J. Skelton, M. A. Starovasnik, Proc. Natl. Acad. Sci USA 2001, 98, 5578-5583]. We have been able to design, synthesize and characterize a hairpin based on this motif which incorporates an azobenzene-based photoswitch, that allows for time-resolved folding studies of beta-struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
116
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 35 publications
(14 reference statements)
5
116
0
1
Order By: Relevance
“…In the context of peptides, cis-AMPP has been shown to be a type I′ β-hairpin backbone peptidomimetic, whereas trans-AMPP lies in a planar conformation ( Figure 1B). 35 We hypothesized that, in the context of the Aβ42 peptide, the trans-azobenzene conformer would reduce selfassembly propensity (rate, thermodynamic stability of fibrils), while the cis-conformer would promote β-turn formation resulting in accelerated fibrillization. The position of the AMPP turn was chosen based on models proposed by Tycko and Smith, which place the turn between a D23/K28 salt bridge.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of peptides, cis-AMPP has been shown to be a type I′ β-hairpin backbone peptidomimetic, whereas trans-AMPP lies in a planar conformation ( Figure 1B). 35 We hypothesized that, in the context of the Aβ42 peptide, the trans-azobenzene conformer would reduce selfassembly propensity (rate, thermodynamic stability of fibrils), while the cis-conformer would promote β-turn formation resulting in accelerated fibrillization. The position of the AMPP turn was chosen based on models proposed by Tycko and Smith, which place the turn between a D23/K28 salt bridge.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…16,17,22 NMR analysis of AMPPcontaining peptides by Dong et al has shown that the trans-AMPP moiety in the context of a Trp zipper can form a nonhairpin turn. 35 This implies that β-hairpin formation is not a strict prerequisite for fibril nucleation and that formation of a nonhairpin turn is sufficient to nucleate fibrillogenesis. That trans AMPP facilitates the formation of nonhairpin turns in Aβ is consistent with the spectroscopic data obtained herein, which correlates to solid-state NMR models of Aβ40 proposed by Tycko and co-workers that predict a nonhairpin turn within the putative turn region.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others (8)(9)(10) have recently focused on the design of photocontrolled ␤-hairpin peptides. To enable an ultrafast initiation of ␤-hairpin folding and unfolding the azobenzene derivative 3-(3-aminomethylphenylazo)phenylacetic acid (AMPP) was used as a reversible light switch (8,10), which, in the cis isomeric state, acts as ␤-turn mimetic (see Fig. 1A).…”
mentioning
confidence: 99%
“…A general feature of the disastrous conformational changes is a transition from native and "healthy" structures to |3-extended precursors of insoluble fibrils. We have now succeeded in designing, synthesizing and investigating a special Phairpin model [1], where the introduction of a femtosecond light switch in a (3-hairpin peptide allowed the observation of ultrafast structural changes -orders of magnitude faster than in previous experiments on P-structures. We show here that an optical trigger starts a series of picosecond conformational transitions of the pstructure (see Fig.…”
Section: Introductionmentioning
confidence: 99%